Prevalence of canine babesiosis and their risk factors among asymptomatic dogs in the federal capital territory, Abuja, Nigeria. (November 2020) - Obeta, Sylvester S.; Ibrahim, Bashiru; Lawal, Idris A.; Natala, Joseph A.; Ogo, Ndudim I.; Balogun, Emmanuel O.
Abstract: Babesia sp. are intracellular parasitic organisms that affects mainly the red blood cells of most mammals, causing the disease known as babesiosis, and transmitted by ticks. Babesisosis is potentially fatal and a major disease of dogs in Nigeria. Therefore, active and routine surveillance is recommended. In this study, the infection was investigated among apparently healthy domestic dogs in six Area Councils of the Federal Capital Territory (FCT), Abuja, Nigeria with the aim of determining the prevalence of the infection and the associated risk factors. Blood samples were collected from dogs ( n  = 480) at randomly selected households, from September 2015 to August 2016. Data regarding sampling location, sex, age, breed, use, presence or absence of ticks were recorded. Blood smears were prepared, stained with Geimsa stain, and examined under light microscope for Babesia sp. The results showed an overall prevalence of 10.8% Babesia canis infection. The prevalence among dogs examined in the six Area Councils were 6.3%, 12.5%, 10.0%, 12.5%, 11.3%, and 12.5 % for Abaji, AMAC, Bwari, Gwagwalada, Kuje and Kwali Area Council, respectively. The prevalence was highest (12.5%) among dogs from Kwali, AMAC and Gwagwalada, and lowest 5 (6.3%) among dogs from Abaji. Of the infected dogs, 13.7% were females and 8.3%, males. Dogs between 12 < 36 months old had the highest (17.0%) prevalence of infection while those of >60 months of age had the lowest (4.5%). Based on breed, the infection was more prevalent among exotic dogs (12.9%) than cross breeds (9.4%). While none of pet dogs were positive for Babesia canis, prevalence of 11.1% and 11.3% were recorded for guard and hunting dogs, respectively. Tick infestation was recorded for 254 dogs of which 17.3% had Babesia canis while only 3.5% of 226 non-infested dogs were Babesia positive. Babesia infection during the rainy season was 14.6% while 3.5% of dogs were positive during dry season. The data on monthly prevalence showed that August and September had the highest (13.5%) prevalence while January and February had the lowest (2.0%). We conclude that the canine babesiosis in the FCT was significantly dependent on age, use of dogs, tick infestation, and season. Therefore, priorities should be given to these factors while instituting control measures against the infection. Highlights: Prevalence of Babesia canis vogeli infection among dogs in FCT is 10.8%. Risk factors of canine babesiosis includes age, dog use, season and tick vector. There are variations of the infection in six Area Councils of FCT.